Health Literacy Pendidikan seks (Sex Education) Dalam Pencegahan Perilaku LGBT Pada Remaja Di SMPN 12 Kota Padang - DEA CETO FRIZKY; Nindy Audia Nadira; Erick Zicof; Neni Fitra Hayati; Rapitos Sidiq (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2026)
The increase in HIV cases among adolescents in Indonesia continues to rise, with the 15–24 age group accounting for 18.2% of total cases (Ministry of Health RI, 2021). In West Sumatra, the prevalence of LGBT behavior increased by 0.45%, with Padang City recording the highest rate at 0.53%. This condition is influenced by adolescents’ lack of knowledge and limited access to accurate sexual education information. This study employed a descriptive qualitative design using in-depth interviews and observation methods. Informants were selected through purposive sampling, consisting of at-risk students (main informants), guidance and counseling teachers (key informants), and peer group members active in school organizations (supporting informants). The results of the study show that at-risk students have limitations in accessing and understanding accurate information about sexual education. They tend to obtain information from social media and experience distorted perceptions of LGBT. In contrast, non-risk students are more critical in filtering information and are open to discussions with teachers. This study resulted in the design of an educational media in the form of a “Dart Board” game as a learning tool. In conclusion, the level of health literacy among adolescents at SMPN 12 Padang is considered adequate in terms of accessing information, but remains low in understanding, evaluating, and applying the information. It is recommended that the school implement game-based educational media as a promotive intervention strategy that aligns with social and health norms.